Statements of ECB Officials and their Effect on the Level and Volatility of the Euro-Dollar Exchange Rate - David-Jan Jansen; Jakob de Haan (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper studies the reaction of the mean and volatility of the euro-dollar exchange rate to statements of ECB officials during the first years of EMU. We focus on statements on monetary policy and the (potential) strength of the euro. We find that the Bundesbank has dominated the news coverage. We conclude that ECB statements have mainly influenced volatility. In some cases there are effects of statements on the level of the euro-dollar rate. Efforts to talk up' the euro have not been successful. There is also evidence of asymmetric reactions to news.
Keywords: 330; ECB; euro; foreign exchange; news approach